1994
DOI: 10.1177/0013164494054001022
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Actual Weight from Self-Report Data

Abstract: Due to reasons of economy of time and ease of data collection, researchers increasingly use self-report weight as a substitute for measured or actual weight. Little research has been done on the inclusion of attitudinal scales and other self-report data in improving prediction of actual weight. The present study examined self-report data as well as actual weight for a sample of 946 young women inductees to the Israel Defense Forces. The results showed that self-reported weight is the best predictor of actual w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This finding suggests that care needs to be taken when using selfreported attendance rates as a proxy for actual attendance rates. Similar biases in self-reporting have been noticed in many other contexts including for example self-reporting of weight (Koslowsky et al 1994).…”
Section: Discussionsupporting
confidence: 72%
“…This finding suggests that care needs to be taken when using selfreported attendance rates as a proxy for actual attendance rates. Similar biases in self-reporting have been noticed in many other contexts including for example self-reporting of weight (Koslowsky et al 1994).…”
Section: Discussionsupporting
confidence: 72%
“…However, at least in the case of self‐reports of weight, heavier individuals may be likely to underreport rather than overreport their weight. For example, a study by Koslowski, Scheinberg, Bleich, and Mark (1994) found that participants who weighed more tended to underreport their weight. In light of this tendency for heavier individuals to underreport their weight, it is likely that we would find even stronger moderating effects of gender in the relationship between body weight and psychological well‐being if BMI had been measured directly.…”
Section: Discussionmentioning
confidence: 99%
“…Both men and women tend to overreport their heights (e.g., Bogaert & McCreary, ; Palta, Prineas, Berman, & Hannan, ) and underreport their weights (Betz, Mintz, & Speakmon, ; Koslowsky et al., ; Palta et al., ). However, men tend to overreport their heights to a greater extent than do women, and women tend to underreport their weights to a greater extent than do men.…”
Section: Height and Weightmentioning
confidence: 99%